2018
DOI: 10.1007/s11325-018-1727-2
|View full text |Cite
|
Sign up to set email alerts
|

REM obstructive sleep apnea: risk for adverse health outcomes and novel treatments

Abstract: Rapid eye movement (REM) sleep was discovered nearly 60 years ago. This stage of sleep accounts for approximately a quarter of total sleep time in healthy adults, and it is mostly concentrated in the second half of the sleep period. The majority of research on REM sleep has focused on neurocognition. More recently, however, there has been a growing interest in understanding whether obstructive sleep apnea (OSA) during the two main stages of sleep (REM and non-REM sleep) leads to different cardiometabolic and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 108 publications
0
51
0
2
Order By: Relevance
“…In the current study, the ESS was lower in REM-predominant OSA than in NSS-OSA and was independently associated with REM-predominant OSA after adjusting for demographics, BMI, and PSG parameters. Although sleepiness usually correlates with OSA severity, 27 studies that assessed patients with REM-related OSA reported less association with daytime sleepiness. 27 – 29 However, there is no consistency on data related to sleepiness in REM-related OSA; a clinic-based study of 1821 subjects who underwent both PSG and multiple sleep latency reported that after adjusting for age, sex, BMI, and the duration of NREM and REM sleep, the REM-related OSA severity was not associated with daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the ESS was lower in REM-predominant OSA than in NSS-OSA and was independently associated with REM-predominant OSA after adjusting for demographics, BMI, and PSG parameters. Although sleepiness usually correlates with OSA severity, 27 studies that assessed patients with REM-related OSA reported less association with daytime sleepiness. 27 – 29 However, there is no consistency on data related to sleepiness in REM-related OSA; a clinic-based study of 1821 subjects who underwent both PSG and multiple sleep latency reported that after adjusting for age, sex, BMI, and the duration of NREM and REM sleep, the REM-related OSA severity was not associated with daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…Although sleepiness usually correlates with OSA severity, 27 studies that assessed patients with REM-related OSA reported less association with daytime sleepiness. 27 – 29 However, there is no consistency on data related to sleepiness in REM-related OSA; a clinic-based study of 1821 subjects who underwent both PSG and multiple sleep latency reported that after adjusting for age, sex, BMI, and the duration of NREM and REM sleep, the REM-related OSA severity was not associated with daytime sleepiness. 29 Similarly, in the Sleep Heart Health Study, REM-related OSA was not associated with daytime sleepiness measured by the ESS after adjusting for demographics, BMI, and NREM-AHI.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the study, we distinguished between obstructive respiratory events occurring in REM and non-REM sleep. Recent attention has focused on the clinical significance of obstructive respiratory events occurring during REM sleep [21]. REM-related OSA was found to be an independent risk factor for cardiovascular disease [22] and diabetes [23], although no such association was found for dyslipidemia [24].…”
Section: Discussionmentioning
confidence: 99%
“…REM-related OSA was found to be an independent risk factor for cardiovascular disease [22] and diabetes [23], although no such association was found for dyslipidemia [24]. REM sleep is characterized by increased sympathetic activity and decreased muscle tone compared to non-REM sleep, and in addition, there is an altered production of some hormones such as the growth hormone or thyrotropin between the two phases of sleep [21]. However, in our study, we did not find a statistically significant difference between AHIREM and AHINREM sleep phases in the prevalence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ABPM recordings give little detailed information over the night-time period, since both micro-and macrostructure of the sleep are not recorded. This is of clinical relevance since respiratory events during REM sleep are associated with higher BP surges (Sasaki et al, 2018) and are thought to be especially relevant for the cardiovascular risk of OSA patients (Mokhlesi et al, 2015;Mokhlesi and Varga, 2018;Varga and Mokhlesi, 2019). Missing BP recordings during REM periods due to large intervals might therefore generate nocturnal BP values that might not reflect reality.…”
Section: Introductionmentioning
confidence: 99%